Title III, Higher Education Act : Issues for Reauthorization by the 102nd Congress. (U.S. Congressional Research., 1991)
Reviews programs under Title III of the Higher Education Act providing Federal financial assistance to strengthen institutions of higher education, particularly those serving needy and minority students. Discusses the appropriations history of Title III programs, 1966-91, and issues for reauthorization, including eligibility criteria, funding formula, and use of reservations and set-asides.